Fortification of yoghurt drink with microcapsules loaded with Lacticaseibacillus paracasei BGP-1 and guaraná seed extract. (February 2022) - Silva, Marluci P.; da S. Mesquita, Mércia; V. Rubio, Fernanda T.; Thomazini, Marcelo; Favaro-Trindade, Carmen S.
Abstract: The influence of co-encapsulation of guaraná seed extract (GSE) and Lacticaseibacillus paracasei BGP-1 on the viability of the bacteria and stability of phenolic compounds during storage of microcapsules and after their application in a yoghurt drink was studied. Co-encapsulation of the potential probiotic and GSE protected the phenolic compounds, with final retention of around 88%, and enhanced the viability of L. paracasei BGP-1 during storage. Concerning the yoghurt formulations, microencapsulation prevented post-fermentation and masked the bitter taste of GSE. As a result, the overall acceptability of yoghurt containing microcapsules was higher than that containing free GSE. In addition, encapsulation and association of GSE allowed for maintenance of L. paracasei counts of about 7 log cfu g −1 in yoghurt formulations stored at 7 °C for up 28 days. Therefore, co-encapsulation represents a valuable tool for the application and protection of functional ingredients in yoghurt drinks.